Quality of life factors in transplant patients - Leite, Alana Mirelle Coelho; Sousa, Patrícia Shirley Alves; Costa, Joice Requião; Melo, Rosana Alves de; Carvalho, Ferdinando Oliveira; Moura, José Carlos de (Revista Cuidarte, 2019)
Introduction: Organ transplantation is a surgical procedure considered as an effective treatment for terminal illness. Performing a transplant may improve the quality of life of patients as well as in the different factors that may interfere with this perception. This study aims to evaluate the influence of socioeconomic factors inherent to the transplant on the perception of the quality of life in patients who have undergone organ transplants. Materials and Methods: A descriptive, quantitative, cross-sectional study was conducted by means of a socioeconomic questionnaire and a quality of life questionnaire, the World Health Organization Quality of Life- BREF. The sample consisted of 258 participants. Mann-Whitney U and Kruskal-Wallis tests were conducted as well as the Spearman’s correlation. The level of significance adopted was p
Keywords: Health Profile; Nursing Care; Health Education; Health Evaluation; Surveys and Questionnaires